Laboratory Ordering Practices in Pregnancy Induced Hypertension and Association of Haematological, Coagulation and Biochemical Parameters with the Severity of Pre-eclampsia - Christian, Jenish; Gupta, Monica (Annals of Pathology and Laboratory Medicine, 2025)
Background: Pregnancy induced hypertension (PIH) is a commonly encountered complication. The study aimed to evaluate the laboratory ordering practices for PIH at Shree Krishna Hospital (SKH), Karamsad to assess adherence to recommended guidelines for test ordering in PIH. By doing so, the study aims to standardize these practices across the Obstetrics and Gynaecology Department (OBGY). The study involves assessing laboratory parameters to differentiate between mild and severe pre-eclampsia. To evaluate the laboratory ordering practices in patients of pregnancy induced hypertension at the Department of Obstetrics and Gynaecology, Shree Krishna Hospital, Karamsad. To assess the association of haematological, coagulation and biochemical parameters with the severity of pre-eclampsia. Methods: A retrospective and prospective observational study (DeC'22-Mar'24) included women with singleton pregnancies at 32-40 weeks gestation. Women with multiple pregnancies, chronic conditions, or a history of cardiac, liver, or renal disease were excluded. A total of 85 (30 mild and 55 severe PIH cases) participated in the study. The test ordering practices were assessed against FOGSI (Federation of Obstetric and Gynaecological Societies of India) guidelines. A perception survey was conducted targeting the residents and consultants of the OBGY Dept at SKH. Results: The study demonstrated variable adherence to the recommended FOGSI guidelines. For coagulation tests 15.29%, for Serum Electrolytes 62.35% and for Urine Protein 84.70% compliance rate with guidelines was found. An amount of 89,050.0 Indian rupees was spent on additional laboratory tests. Survey response indicated that tests are often ordered "just to be safe". The statistical significance was found for haemoglobin, ALT, AST, and LDH levels between mild and severe PIH cases. Conclusion: The study emphasizes a need for an improvement in managing PIH through better adherence to laboratory ordering guidelines as there was a notable inconsistency in following established protocols for laboratory testing that resulted in over utilization. The overall cost of these over-ordered tests was substantial enough (89,050 Rs) to impact both the hospital and the patients.